2017
DOI: 10.1089/thy.2016.0411
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofRETMutations in Multiple Endocrine Neoplasia 2 in Denmark 1994–2014: A Nationwide Study

Abstract: Background: Germline mutations of the REarranged during Transfection (RET) proto-oncogene cause multiple endocrine neoplasia 2 (MEN2). It is unclear whether the distribution of RET mutations varies among populations. The first nationwide study of the distribution of RET mutations was conducted, and the results were compared to those of other populations.Methods: This retrospective cohort study included 1583 patients who underwent RET gene testing in one of three centers covering all of Denmark between Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…This retrospective cohort study included 12 unique MEN2B patients identified through the following sources: 1. A nationwide RET cohort containing all patients (n = 1583) RET tested in Denmark from 1994 to 2014 (Mathiesen et al 2017b). Eight MEN2B patients were identified from this source.…”
Section: Dear Editormentioning
confidence: 99%
“…This retrospective cohort study included 12 unique MEN2B patients identified through the following sources: 1. A nationwide RET cohort containing all patients (n = 1583) RET tested in Denmark from 1994 to 2014 (Mathiesen et al 2017b). Eight MEN2B patients were identified from this source.…”
Section: Dear Editormentioning
confidence: 99%
“…An original national cohort comprising all patients tested for RET mutations in Denmark from September 1994 to December 2014 was extended to October 2017 . This combined cohort was then searched for carriers of RET Y791F.…”
Section: Methodsmentioning
confidence: 99%
“…Carriers were excluded if harboring an additional RET variant acknowledged as pathogenic in the ARUP MEN2 database as per October 1st, 2018 . The methods of genomic testing have been previously reported and still apply …”
Section: Methodsmentioning
confidence: 99%
“…In Denmark, RET testing has been available since September 1994. 8 Seven years later, in February 2002, the first Danish guidelines, recommending RET testing of all patients with MTC, were published. 9 In the meantime, it is unknown if these guidelines have improved completeness of RET testing in MTC patients.…”
Section: Introductionmentioning
confidence: 99%